Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Systematic identification pepper CaE2F transcription factor reveals the role of CaDPb in drought stress response - Rong Lu; Yishui Chen; Longxue Li; Zilin Zhang; Qinghong Zhou; Meixia Wang; Huibin Han (Plant Science, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Unraveling the short- and long-term effects of lignocellulosic pretreatment derivatives on the anaerobic co-digestion of corn straw and food waste: Digester performance, microbial community, and metabolic mechanisms - Sifan Cao; Yong-Chen Han; Xiaochang C. Wang; Rong Chen; Bao-Shan Xing (Bioresource Technology, 2026)

Shrub encroachment drives multifunctionality trade-offs by reorganizing plant and microbial communities in an alpine meadow - Yang Liu; Hong Xiao; Yuping Rong; Changlin Xu; Ao Han; Kai Ma; Yun Wang (Agriculture, Ecosystems & Environment, 2026)

A sustained-release gallic acid microcapsule suspension for simultaneous inhibition of Microcystis aeruginosa and control of microcystin release - Yu Yin; Kaipian Shi; Ziyu Rong; Conghui Wang; Jinyu Han; Shiyin Li; Li Yin (Journal of Environmental Chemical Engineering, 2026)

Stoichiometric shifts drive divergent growth responses to chronic nitrogen addition between young and older plantations - Huihui Liu; Tingting Ren; Xiaoming Zou; Han Y.H. Chen; Rong Huang; Yu Fang; Guobing Wang; Honghua Ruan (Forest Ecology and Management, 2026)

Field measurements of the structural response of a linked twin-tower super-tall building during two typhoons - Liang Han; An Xu; Jiyang Fu; Yangxue Wang; Hua Rong; Wei Shi; Lele Zhang (Engineering Structures, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Removal efficiency and mechanisms of natural mineral materials for bacteriophages MS2 and ΦX174 in aqueous environments - Ying Song; Ya-ting Wang; Ying Han; Rong-xuan Xu; Yang Wang; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Plant litter enhances hexabromocyclododecane removal in riparian zones at high water level: Insights from the coupling of microbial dehalogenation and carbon cycling - Rong Wang; Juan Chen; Li Wang; Han Gao; Qihao Nie; Shunqing Zhang; Qiming He (Water Research, 2026)

Mechanical behaviour, deformation mechanisms and support optimization of tunnels in gentle dip layered rock after freeze–thaw cycles - Xiao-Hu Zhang; Jia-Bing Zhang; Jun-Bin Fu; Rong-Huan Du; Han-Lin Wang (Tunnelling and Underground Space Technology, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

Synthesis, characterization and application potential of recombinant chicken (Gallus gallus) ferritin with excellent iron-binding capacity and stability - Min Huang; Ranran Pang; Xiaojing Liu; Kai Zhou; Rong Sheng; Yuanyuan Wang; Changyuan Han; Binbin Xu; Han Li; Baocai Xu (Food Bioscience, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Role of pyroptosis in melanoma: Molecular mechanisms and therapeutic potentials - Xiao-Han Zhang; Ke Zhang; Xue-Chun Qu; Jing Zhang; Umm E. Laila; Bo Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Application of optimized hydrothermal, ozone and superalkali pretreatment techniques for qualitative biogas production from corn straw: A comparative assessment - Sifan Cao; Yong-Chen Han; Huqe Farhana; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Fuel, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Exploring root-mediated Erwinia amylovora invasion mechanism in Korla fragrant pear (Pyrus sinkiangensis) - Lili Han; Yue Sun; Xin Deng; Jiehua Wang; Feng Zhang; Weimin Chen; Rong Lei (European Journal of Plant Pathology, 2026)

Pentoxifylline targets TLR4/MyD88/NF-κB signaling to ameliorate neuroinflammation and metabolic dysfunction in a rat model of chronic hypoperfusion-induced vascular cognitive impairment - Xiaohan Wang; Bingchuan Xie; Xiaoyang Yuan; Jiaying Rong; Xiaojing Lv; Qingying Ma; Li Shen; Bing Han (Metabolic Brain Disease, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Organic fertilizer substitution combined with Bacillus velezensis SQR9 inoculation reduces carbon footprint and enhances net eco-economic benefits in tropical vegetable fields - Wei Tian; Huacheng Yin; Ziheng Zou; Rong Li; Yawen Huang; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Journal of Environmental Management, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Mapping coastal aquaculture ponds in China without dependence on water levels: New insights from pond dikes derived from Sentinel-1/2 imagery - Chuanpeng Zhao; Mingming Jia; Rong Zhang; Quan Han; Chunying Ren; Zongming Wang (Environmental Impact Assessment Review, 2026)

Advances in the regulation of NLRP3 inflammasome by natural polysaccharides: Structural features, mechanisms of action, and disease associations - Xuebin Xu; Rong Ji; Hua Huang; Jiufu Xiao; Han Zhang; Haixue Kuang; Zhibin Wang (Carbohydrate Polymers, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

Archaeal and Bacterial Communities and Their Relations with Hydrochemistry in Gongzhu Co, a Carbon-Poor, Nutrient-Rich Basin Lake of the Qinghai–Xizang Plateau - Minhaoxue Zou; Yujie Tao; Bohan Shi; Rong Xu; Rong Wang; Yongzhen Li; Rui Han; Derui Zhu (Current Microbiology, 2026)

Structural characterization and anti-aging mechanism of Codonopsis pilosula polysaccharides - Meiqi Wan; Rong Han; Xiaoai Bao; Yizheng Sun; Hailong Xu; Yanlin Wang; Aihong Zhao; Youbo Zhang (Food Research International, 2026)

Livestock grazing modulated the effects of flooding on ecosystem multifunctionality in the wetland of the lower Tumen River in Northeast China - Linguang Luan; Mingyue Pan; Yingqi Han; Qiong Han; Lin Yuan; Rong Liu; Weihong Zhu; Jingzhi Wang (Environmental Research, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Stochastic and deterministic processes shape microbiota and flavors of strong-flavor Daqu made from different wheat varieties during fermentation - Kangjie Yu; Rong Yang; Huiling Huang; Shuanghui Wang; Chaojiu He; Liya Huang; Yi Ma; Dejun Han (Food Research International, 2026)

Antibacterial mechanism of Sanguinarine against Klebsiella pneumoniae and its efficacy in reducing bacterial contamination in milk - Ruiying Wang; Diangang Han; Tianlong Hu; Rong Zhao; Yanlin Li; Qiqi Pu; Ju Zeng; Xiong Dai; Long Zhang; Jige Xin (Food Bioscience, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

Soil amendments improved physiological characteristics, grain yield, and water use efficiency of common buckwheat under multi-year continuous cropping - Qi Wang; Xiaoyi Han; Qixuan Wang; Minlong Du; Xinyue Lei; Jiahao Ge; Rong Zhong; Chenxi Wan; Xiaoli Gao; Pu Yang; Jinfeng Gao (European Journal of Agronomy, 2026)

Crop rotation benefits for nitrogen-oxide mitigation and soil health in tropical vegetable fields - Wei Tian; Feilong Liang; Rong Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Agriculture, Ecosystems & Environment, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Microbial-mediated nitrogen transformations alter N2O emissions at the scale of soil aggregates from abandoned farmlands - Rong Wang; Yixian Ruan; Runhao Shi; Sihan Wang; Yayun Yang; Bo Zhang; Linzi Lou; Hongjian Hao; Xinhui Han; Wei Zhang (Pedosphere, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

A bioinspired integrated aerogel evaporator for ultra-high power and sustainable electricity generation - Yutong Huang; Denan Kong; Weitong Chen; Wenjie Dou; Ning Zhang; Rong Chen; Shengze Hu; Xu Han; Xianbao Wang; Quanzhen Zhang; Teng Zhang; Baofei Hou; et al. (Chemical Engineering Journal, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

Tuning Fe-P covalency via regenerative phosphorus vacancies for efficient aqueous cyclohexanone degradation - Han Feng; Zhengyi Lu; Ming Chen; Changming Zhong; Yongquan Wang; Rong Lin; Wenfeng Xu; Junming Hong (Environmental Research, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Microbial mechanisms of biochar reducing methane emission in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Baoli Qin; Ting Yang; Rong Xu; Lingyu Zhu; Guangming Han; Leiming Wu; Siyu Li; Jianhua Bi; Shouhong Wang; Jiahong Zhang; et al. (Journal of Environmental Management, 2025)

Synergistic interfacial engineering and ion transport kinetics in high-safety PEO-based polymer electrolytes - Hong-Yu Wang; Kun-Rong Lu; Yue-Xi Han; Fa-Nian Shi; Peng-Fei Wang; Yu-Hang Zhang (Chemical Engineering Journal, 2025)

Novel multi-component synergistic bioink that balances biocompatibility and mechanical strength for cartilage regeneration - Zijun Ma; Wendan Jia; Xiaoyuan Wang; Rong Cheng; Lu Han; Meng Li; Xiaoning Yang; Shengbo Sang (Journal of Zhejiang University-SCIENCE B, 2025)

Biocontrol Effects and Potential Defence Mechanism of Bacillus velezensis JS6-1 Against Fusarium solani-Induced Postharvest Rots in Muskmelon - Yafang He; Jiayi Wei; Fushuang Chen; Ning Wang; Yajie Han; Zifei Wu; Xingwen Wang; Faqiang Zhan; Yingwu Shi; Rong Yang; Huifang Bao (Current Microbiology, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Performance evaluation of EAF dust-loaded rice straw biochar as the EAF foaming agent: Study on physicochemical properties and reduction behavior with slag - Chengjin Han; Guangsheng Wei; Qisheng Wang; Rong Zhu (Fuel, 2025)

From photosynthesis to grain formation: A comprehensive evaluation of nitrogen-phosphorus co-optimization strategies in mung bean (Vigna radiata L.) cultivation - Jiahao Ge; Xiaoyi Han; Qi Wang; Rong Zhong; Shaofei Li; Qixuan Wang; Enlei Li; Qingming Wang; Feng Gao; Baili Feng; Jinfeng Gao (Field Crops Research, 2025)

How root exudates of vegetation contribute to prevention and control of soil disintegration on Chinese Loess Plateau: A case study of Robinia pseudoacacia L. - Tao Xiao; Ping Li; Rong Jiang; Sai K. Vanapalli; Xiangcheng Han; Hui Zhai; Yiyi Yang; Qi Gu; Jiading Wang (Engineering Geology, 2025)

Layered manure enhances root development via soil hydrothermal optimization in ridge tillage - Bo Kang; Xun Yan; Yingjie Zhang; Rong Huang; Youlin Luo; Qiang Xu; Lihong Han; Changquan Wang; Bing Li (Plant and Soil, 2025)

Non-linear and contrasting responses of abundant, intermediate and rare prokaryotic phylotypes to environmental gradients in forests of East China - Guangxin Wang; Shuhan Zhang; Bin Hua; Rong Mao; Yang Zhang; Anton A. Goncharov; Ximei Zhang; Xingguo Han; Wei Yang (Applied Soil Ecology, 2025)

Fluoride Induces Spermatogonial Apoptosis via IP3R-MCU-Mediated Mitochondrial Calcium Overload - Rong Wang; Han Wang; Wenjing Gong; Xiaoqian Chen; Mengli Zheng; Ya Cui; Chunmei Liang; Jiayue Hu; Yuanhua Chen; Yanli Ji (Biological Trace Element Research, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Dual regulation of surface electronegativity and interlayer structural feature in fluorinated COFs for efficient gold recovery - Xiaoning Zhan; Yucheng Jin; Bin Han; Dongdong Qi; Chunli Li; Rong Jiang; Xiaonan Pang; Guoqing Xu; Mingyue Wang; Qi Zhang; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Applications and challenges of modified algal biochar in environmental remediation - Yan Sun; Chunxiao Hao; Yongjie Wang; Huan Zhong; Song Zhou; Han Meng; Huan He; Pei Lei; Nan Rong (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Neuroprotective Effects, Mechanisms of Action and Therapeutic Potential of the Kv7/KCNQ Channel Opener QO-83 in Ischemic Stroke - Huiran Zhang; Yanfei Tian; Yan Zhang; Yan Wang; Jinlong Qi; Xiangyu Wang; Yi Yuan; Rong Chen; Yupeng Zhao; Chang Liu; Najing Zhou; Lanxin Liu; et al. (Translational Stroke Research, 2025)

Identification and Functional Analysis of Trehalose Synthesis Genes in Foxtail Millet: Insights into Low-Temperature Stress Response - Yueyue Wang; Yajun Li; Yidan Luo; Yuhua Xu; Bo Zhao; Rong Sun; Juan Zhao; Xukai Li; Yijuan Zhang; Yuanhuai Han; Hongying Li; Hui Zhang (Journal of Plant Growth Regulation, 2025)

Comparative analysis of multiple machine learning models: identifying impact factors in biochar heavy metal adsorption mechanisms - Zixin Zeng; Yingdong Wu; Wenjie Li; Lei Han; Huangshiyu Zhao; Rong Teng; Han Yuan; Ziang Wang; Sijia Li (Environmental Geochemistry and Health, 2025)

Elucidation of the anti-fibrotic diseases mechanism of chelerythrine by integrative approach of network pharmacology and experimental verification - Wei Han; Gui-yun Qian; Qin-rong Wang; Jie Liu; Yong-ping Zhang; Jian Xu; Tingting Li; Zhe Li (Natural Product Research, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

Mechanisms of naphthalene biodegradation in microalgal-bacterial co-culture systems: role of photosynthesis, antioxidant and extracellular polymeric substances - Mengying Wang; Han Wang; Xuetao Liang; Lingyun Rong; Longyan Cui; Chen Wang; Sixu Wang; Qi Yang; Zhilin Yang (Journal of Cleaner Production, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Dual-phased nickel sulfide heterojunction of Ni9S8/Ni3S2 doped with Co assembled on Ni foam as a highly efficient electrocatalyst for alkaline oxygen evolution reaction - Siqi Zhang; Chaonan Wang; Wenyi Peng; Jiahao Huang; Senkai Han; Siao Li; Rong Liu; Shulan Ma; Huiqin Yao (Chemical Engineering Journal, 2025)

A natural 294-bp indel in the VviHKT1;1 proximal promoter influences the salt resistance of VviHKT1;1-overexpressing Arabidopsis - Fengjie Wang; Xiaoying Gong; Xuenan Zhang; Rong Zhao; Ning Han; Zhen Yang (Journal of Plant Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Microplastics impair wound healing via NAT10-mediated epigenetic dysregulation of FASN-PI3K/AKT signaling - Feng-Jie Shen; Wei-Nan Cao; Xue-Chun Han; Qiu-Yue Pan; Yuan Wang; Rong Zhang; Gang Wei; Jin-Kui Yang (NanoImpact, 2025)

Conceptualization and assessment of groundwater–seawater interactions on bedrock islands - Rong Gong; Dongmei Han; Yi Xiao; Xianfang Song; Wei Wang; Yanling Cao (Journal of Hydrology, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Tuning ligand defect in porphyrins metal-organic frameworks to boost electrochemiluminescence for sensitive detection of amyloid-β1-42 - Jinyan Li; Xiaoqi Pei; Rong Qu; Lei Liao; Wen Zhang; Zhen Wang; Gang Xie; Sanping Chen; Jing Han (Chemical Engineering Journal, 2025)

Cerium oxide nanoparticles ameliorate Arabidopsis thaliana root damage under UV-B stress by modulating the cell cycle and auxin pathways - Cheng Sun; Chen Zhao; Guohua Wang; Rong Han (Protoplasma, 2025)

Fragmentation pattern-based nontargeted screening strategy uncovered novel halogenated nucleotides in drinking water - Guangrong Sun; Pei Guo; Rong Liu; Han Yeong Kaw; Wei Wang (Journal of Hazardous Materials, 2025)

Integration of comparative cytology, ionome, transcriptome and metabolome provide a basic framework for the response of foxtail millet to Cd stress - Jie Zheng; Xinyue Wang; Rong Huang; Peiyu Xian; Jian Cui; Aduragbemi Amo; Liang Chen; Yuanhuai Han; Siyu Hou; Yang Yang (Journal of Hazardous Materials, 2025)

Adsorption behavior and mechanism of cadmium, copper, and lead on polylactic acid microplastics exposed to ultraviolet light - Fang Feng; Shutao Wang; Xue He; Xinghua Wang; Jia Huang; Guiming Liu; Sashuang Rong; Shiming Su; Hongyuan yan; Bing Han; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Mechanistic study of ultrasound synergy with soybean 11S globulin to improve myofibrillar protein gel properties in low-salt lamb: molecular conformation and water migration - Rong Bai; Jing Xi; Huiyu Han; Rakhimova Aidana; Aitmagambetova Madina; Shengqi Jiang; Xiang Ye; Chunjie Yang; Siying Wang; Wu Ding (Food Research International, 2025)

Extraction of hydroxy safflower yellow A and anhydroxysafflor yellow B from safflower florets using natural deep eutectic solvents: Optimization, biological activity and molecular docking - Chun-Ying Wu; Bao-Rong Wang; Si-Yi Han; Ying-Hua Zhang; Zhi-Shen Mu (Food Bioscience, 2025)

Hydrolytic degradation of nerve agent simulants accelerated by host-guest gold nanozymes - Qingqing Sun; Mengyuan Wang; Qingqing Wen; Haili Dong; Yanchao Lyu; Jie Han; Rong Guo (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Transcriptome and Metabolome Combine to Analyze the Mechanism of Leaf Coloration Formation in Aeonium arboreum ‘Pink Sybil’ - Suhua Li; Rong Zhao; Haozhang Han; Lihua Zhang; Fang Wang; Nan Zhang; Rong Dong (Plant Molecular Biology Reporter, 2025)

Creating a novel engineered tobacco chassis with downregulated expression of β-1,2-xylosyltransferase - Rong Han; Anran Xu; Yangzhong Wang; Jing Cao; Muhammad Naeem; Weihua Zhao; Lingxia Zhao (Journal of Plant Biochemistry and Biotechnology, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Identification of key risk ships in risk-based ship complex network - Qian Qiao; Rong Zhen; Han Dong; Shuwu Wang; Qionglin Fang (Ocean Engineering, 2025)

Enhanced microbial degradation of hexabromocyclododecane in riparian sediments through regulating flooding regimes - Juan Chen; Rong Wang; Chao Wang; Peifang Wang; Han Gao; Yu Hu; Qihao Nie; Shunqing Zhang (Journal of Hazardous Materials, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Preparation of sodium alginate/pectin/cellulose nanofibrils films containing black soybean seed coat anthocyanins for monitoring goat meat freshness - Siying Wang; Xinyue Han; Ya Chen; Yikai Shao; Jiaqing Song; Chunjie Yang; Shengqi Jiang; Rong Bai; Xiang Ye; Wu Ding (Food Control, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Double-network hydrogel dressing regulated by cationic polymer-grafted bacterial cellulose for promote rapid healing of infected wounds - Xuhui Rong; Guoliang Gao; Jiang Lou; Xiaolei Wang; Wenjia Han (Carbohydrate Polymers, 2025)

A multi-perspective understanding of population change in migratory species: A case study with pied avocets (Recurvirostra avosetta) in East Asia - Yang Wu; Weipan Lei; Entao Wu; Han Pan; Yifei Jia; Cai Lu; Yongxiang Han; Junjie Wang; Rong Fan; Zhijun Ma; Zhengwang Zhang; Richard A. Fuller (Biological Conservation, 2025)

Archaeal and Bacterial Communities Within the Wetland Alkaline Har Lake of the Qinghai-Xizang Plateau - Yujie Tao; Bohan Shi; Minhaoxue Zou; Lijuan Qiao; Rong Wang; Derui Zhu; Rui Han (Current Microbiology, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

A Global Synthesis of How Plants Respond to Climate Warming From Traits to Fitness - Pengyan Jia; Rong Zhang; Bernhard Schmid; Han Wang; Jin‐Sheng He; Jiaxi Liu; Sijie Liu; Sipeng Jian; Yanhao Feng (Ecology Letters, 2025)
Despite intensive research, our understanding of how plants respond to warming by coordinating their full arsenal of traits to adjust fitness is lacking. To fill this gap, we applied a trait‐based framework with three clusters (two functional clusters: “carbon‐fixation rate” and “carbon‐fixation area”; a third cluster: “total carbon fixation”) to a global dataset compiled from 572 studies of warming experiments with 677 species and a comprehensive list of traits and fitness components. The pairwise correlation analysis complemented with SEM and PCA showed that plants increased biomass (the core variable in the third cluster) under warming by coordinating satellite traits in two functional clusters to adjust their core traits, net photosynthesis rate and total leaf area, respectively. In particular, the trait coordination was characterised by the maintenance of net photosynthesis rate and the increase of total leaf area, which was robust across ecological contexts although warming responses of the variables per se displayed context‐dependences. Moreover, the trade‐offs between biomass and reproduction (itself bearing mass vs. number trade‐offs) in their warming responses scaled the coordination to enhance fitness except in the contexts where reproduction was reduced. These findings could help explain and predict plant form and function in a warming world.

Jarosite residues recycling by slurry electrolysis: Iron recovery and detoxification in one step - Rong Wang; Mengjun Chen; Wei Fan; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Process Safety and Environmental Protection, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Auxin regulates leaf senescence and nitrogen assimilation to promote grain filling in maize (Zea mays L.) - Na Jiang; Peng Wang; Zhiqi Yang; Changwei Li; Yixiang Xia; Xiangmin Rong; Yongliang Han; Lan Yang (Field Crops Research, 2025)

Recent advancements in cation-intercalated vanadium oxide cathode materials for zinc-ion batteries - Kunxuan Li; Rong Li; Tiantian Guan; Lei Wang; Lingling Xie; Qing Han; Xuejing Qiu; Xiaoyu Cao; Limin Zhu (Chemical Engineering Journal, 2025)

Study on the pyrolysis kinetics of rice husk catalyzed by zinc-containing oxides in electric arc furnace dust - Chengjin Han; Guangsheng Wei; Qisheng Wang; Rong Zhu; Fuhai Liu (Biomass and Bioenergy, 2025)

Soil moisture drought and diverse impacts on vegetation across the Tibetan Plateau in recent three decades - Yongwei Liu; Xingwang Fan; Wen Wang; Han Zhou; Chengmei Luan; Ruonan Wang; Rong Wang; Yuanbo Liu (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Advances on jarosite residue detoxification and reutilization: a review - Mengjun Chen; Rong Wang; Wei Fan; Jiqin Wang; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Environmental Science and Pollution Research, 2025)

Epilimnetic oligotrophication increases contribution of oxic methane production to atmospheric methane flux from stratified lakes - Fan Xun; Muhua Feng; Cheng Zhao; Wenlei Luo; Xiaotong Han; Zhen Ci; Yifan Yin; Rong Wang; Qinglong L. Wu; Hans-Peter Grossart; Peng Xing (Water Research, 2025)

Optimized acid leaching synthesis and steam regeneration of the steel slag-derived calcium-based sorbent for enhanced CO2 capture - Nai Rong; Xiuliang Shi; Shanshan Wang; Long Han; Kaiwei Liu; Lichao Ge; Yuhan Wang; Geng Wang (Journal of Cleaner Production, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Unraveling the cellular response and detoxification efficiency of microalgal systems to naphthalene contamination in water - Mengying Wang; Han Wang; Lingyun Rong; Qi Yang; Zhilin Yang (Algal Research, 2025)

Transcription factor CcbHLH66 regulates mandarin fruit coloration via modulating the expression of chlorophyll degradation related genes CcRCCR and CcNYC - Huali Wang; Qian Liu; Shufang Deng; Jialin Chen; Jin Han; Rong Zhu; Kaifang Zeng; Lili Deng (Postharvest Biology and Technology, 2024)

Long-term contamination of decabromodiphenyl ether reduces sediment multifunctionality: Insights from nutrient cycling, microbial ecological clusters, and microbial co-occurrence patterns - Han Gao; Juan Chen; Chao Wang; Peifang Wang; Rong Wang; Bingbing Feng (Journal of Hazardous Materials, 2024)

Microscopic mechanisms and durability evaluation under freeze-thaw conditions of heavy metal solidification in red mud-slag geopolymer - Lu Zhou; Xin Xu; Qing Wang; Junboum Park; Yongming Han; Lisheng Guo; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

A coupled regional-scale numerical model for hydrological processes and interactions between groundwater and surface water in a controlled drainage district - Xudong Han; Yan Zhu; Xiugui Wang; Youzhen Wang; Tao Shen; Rong Tang (Journal of Hydrology, 2024)

Macroaggregate is crucial in soil carbon and nitrogen accumulation under different vegetation types in the Loess Plateau, China - Hongjian Hao; Yujie Liang; Duo Pian; Ying Zhang; Yaxian Chen; Hongtao Lai; Zhouchang Yu; Ahejiang Sailike; Rong Wang; Ling Cao; Xinhui Han; Wei Zhang (Forest Ecology and Management, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Rice-crayfish integrated system enhances global warming potential via increasing methane emission mainly driven by continuous deep flooding - Linjie Ma; Chengxin Zhang; Baoli Qin; Jun Yang; Ting Yang; Rong Xu; Guangming Han; Shouhong Wang; Jiahong Zhang; Xiangming Kou (Applied Soil Ecology, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

Development of a method to assess synergy and competition for water use among water-energy-food nexus in the Yellow River basin: Water quantity-quality dimensions - Xinxueqi Han; En Hua; Jiajie Guan; Bernie A Engel; Rong Liu; Yawen Bai; Shikun Sun; Yubao Wang (Journal of Hydrology, 2024)

Adsorption and catalytic degradation of tetracycline hydrochloride by HCNTs /MnFe2O4 - Chunjie Ma; Aaron Albert Aryee; Keke Zhu; Rong Wang; Runping Han (Journal of Environmental Chemical Engineering, 2024)

Exposure, Distribution, and Ecological Risk of Four New Bisphenol Analogs in the Typical Lake Region of Taihu Lake - Ying Han; Yuxuan Liu; Xiaolong Rong; Mingxin Wang; Yingang Xue; Hao Dai; Haixia Jiang (Exposure and Health, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Hydrophilic phthalocyanine covalent organic frameworks for enhanced electrocatalytic H2O2 production - Rong Jiang; Qianjun Zhi; Bin Han; Ning Li; Kang Wang; Dongdong Qi; Wenjun Li; Jianzhuang Jiang (Chemical Engineering Journal, 2024)

A nonlinear elastic-strain hardening model for frozen improved sandy soil under uniaxial compression loading condition - Bo Liu; Yanqing He; Yanhui Han; Guoxuan Wang; Rong Gao; Dongyang Li (Cold Regions Science and Technology, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Recycling drinking water treatment sludge in construction and building materials: A review - Zhi-hai He; Bin Wang; Jin-yan Shi; Hui Rong; Hong-yu Tao; Ahmed Salah Jamal; Xu-dong Han (Science of The Total Environment, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

Vessel intrusion interception utilising unmanned surface vehicles for offshore wind farm asset protection - Yang Gu; Peiji Wang; Zhenwei Rong; Hao Wei; Shujie Yang; Kui Zhang; Zili Tang; Tao Han; Yulin Si (Ocean Engineering, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

Characteristics of bacterial community structure in the sediment of Chishui River (China) and the response to environmental factors - Fei Di; Donghui Han; Guang Wang; Wenbo Zhao; Daokun Zhou; Nan Rong; Shou Yang (Journal of Contaminant Hydrology, 2024)

Efficient Separation of Uranium in Solution by ZnFe2O4 Doped with ZrO2: Adsorption Behaviors and Mechanism Study - Lin Peng; Houzhen Bai; Lishan Rong; Jinxiang Liu; Guohua Wang; Jinsong Wang; Han Xian (Water, Air, & Soil Pollution, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

circRNAs deregulation in exosomes derived from BEAS-2B cells is associated with vascular stiffness induced by PM2.5 - Qingping Liu; Yaling Zhang; Bin Han; Mengruo Wang; Huaifang Hu; Jie Ning; Wentao Hu; Meiyu Chen; Yaxian Pang; Yuanyuan Chen; Lei Bao; Yujie Niu; et al. (Journal of Environmental Sciences, 2024)

A novel heavy-duty truck driving cycle construction framework based on big data - Yuzhou Yang; Xuan Zhao; Xiaolei Yuan; Shu Wang; Lingchen Kong; Qi Han; Rong Huang (Transportation Research Part D: Transport and Environment, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Insights into spirotetramat-induced thyroid disruption during zebrafish (Danio rerio) larval development: An integrated approach with in vivo, in vitro, and in silico analyses - Fang Jiao; Hua Rong; Yang Zhao; Panfeng Wu; Yaohui Long; Jie Xu; Tao Zhao; Lingxi Han; Jun Wang; Huirong Yang (Environmental Pollution, 2024)

Slow-release nitrogen fertilizer reduces input without yield loss in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Rong Xu; Ting Yang; Guangming Han; Leiming Wu; Shouhong Wang; Jiahong Zhang; Qin Yuan; Xiangming Kou (Nutrient Cycling in Agroecosystems, 2024)

Corrigendum to ‘Regulatory mechanisms of submerged macrophyte on bacterial community recovery in decabromodiphenyl ether contaminated sediment: Microbiological and metabolomic perspectives’ [Environ. Pollut. 337 (2023) 122616] - Han Gao; Juan Chen; Chao Wang; Peifang Wang; Rong Wang; Bingbing Feng (Environmental Pollution, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Review: Phytate modification serves as a novel adsorption strategy for the removal of heavy metal pollution in aqueous environments - Xiaoliang Xue; Yuzhu Han; Xinming Wu; Hongji Wang; Shuang Wang; Jiaqi Zheng; Rong Ran; Chaowen Zhang (Journal of Environmental Chemical Engineering, 2023)

Vertical heterojunction photodetector with self-powered broadband response and high performance - Yajie Han; Shujie Jiao; Jiangcheng Jing; Lei Chen; Zehao Shi; Ping Rong; Dongbo Wang; Shiyong Gao; Wen He; JinZhong Wang (Chemical Engineering Journal, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Changes in soil organic carbon stocks of forestlands and grasslands on the Loess Plateau, 1980–2015 - Gang Li; Shaobo Sun; Nan Lu; Rong Huang; Jianwu Yan; Fan Song; Jichang Han; Ying Wang (Journal of Cleaner Production, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Reducing airborne transmission of SARS-CoV-2 by an upper-room ultraviolet germicidal irradiation system in a hospital isolation environment - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong; Hao Han; Lingyun Wang; Desheng Wang (Environmental Research, 2023)

Regulatory mechanisms of submerged macrophyte on bacterial community recovery in decabromodiphenyl ether contaminated sediment: Microbiological and metabolomic perspectives - Han Gao; Juan Chen; Chao Wang; Peifang Wang; Rong Wang; Bingbing Feng (Environmental Pollution, 2023)

Remediation of ibuprofen and naproxen in water by a green composite material of magnetic carbon nanotube–metal–organic framework - Xiaoting Zhang; Chenping Gao; Rong Wang; Runping Han (Journal of Environmental Chemical Engineering, 2023)

Regulating dynamic equilibrium of active hydrogen for super-efficient nitrate electroreduction to ammonia - Yang Gao; Rong Wang; Yudong Li; Enshan Han; Maosen Song; Ziyi Yang; Feng Guo; Yanzhen He; Xiaohui Yang (Chemical Engineering Journal, 2023)

Transcriptome and Metabolome Integrated Analysis Reveals the Mechanism of Cinnamomum bodinieri Root Response to Alkali Stress - Haozhang Han; Lihua Zhang; Suhua Li; Rong Zhao; Fang Wang; Rong Dong; Xiaoli Wang (Plant Molecular Biology Reporter, 2023)

Potential candidate genes and pathways related to cytoplasmic male sterility in Dianthus spiculifolius as revealed by transcriptome analysis - Yingzhu Liu; Han Sun; Rong Ye; Jinxue Du; Haizhen Zhang; Aimin Zhou; Kun Qiao; Jingang Wang (Plant Cell Reports, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Adsorption and catalytic degradation of bisphenol A and p-chlorophenol by magnetic carbon nanotubes - Huihui Gao; Xiaoyu Han; Rong Wang; Keke Zhu; Runping Han (Environmental Research, 2023)

People's psychological and physiological responses to the combined smell-thermal environments - Chao Jia; Yonghua Rong; Xiaoying Geng; Menghan Wang; Zhicheng Zhang; Shengnan Han; Xihao Bie (Building and Environment, 2023)

Remediation of water tainted with noxious aspirin and fluoride ion using UiO-66-NH2 loaded peanut shell - Xiaoting Zhang; Xiaoyu Han; Yang Liu; Runping Han; Rong Wang; Lingbo Qu (Environmental Science and Pollution Research, 2023)

Aquatic photolysis of high-risk chemicals of emerging concern from secondary effluent mediated by sunlight irradiation for ecological safety and the enhanced methods - Danyang Li; Xiaoyan Y. Ma; Shiying Zhang; Yongkun K. Wang; Yingnan Han; Rong Chen; Xiaochang C. Wang; Huu Hao Ngo (Water Research, 2023)

Human milk whey glycoprotein N-glycans varied greatly among different maternal secretor status - Xiaoqin Wang; Wenqing Li; Zhenhua Li; Tianjiao Han; Jinqiao Rong; Jiangbo Fan; Linjuan Huang; Yu Lu; Zhongfu Wang (Carbohydrate Polymers, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Diversity and interaction of bacterial and microeukaryotic communities in sediments planted with different submerged macrophytes: Responses to decabromodiphenyl ether - Han Gao; Juan Chen; Chao Wang; Peifang Wang; Rong Wang; Yu Hu; Ying Pan (Chemosphere, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

Phytotoxicity and the molecular response in yttrium oxide nanoparticle–treated Arabidopsis thaliana seedlings - Jin Wang; Shifeng Zhao; Zhuoxuan Li; Jianxiang Chai; Jinlin Feng; Rong Han (Protoplasma, 2023)

Brachypodium BdCHS is a homolog of Arabidopsis AtCHS involved in the synthesis of flavonoids and lateral root development - Jin Wang; Xiaolei Wang; Shifeng Zhao; Xiaoyu Xi; Jinlin Feng; Rong Han (Protoplasma, 2023)

CRISPR/Cas9-based point-of-care lateral flow biosensor with improved performance for rapid and robust detection of Mycoplasma pneumonia - Rong Zhu; Han Jiang; Chaoyou Li; Yan Li; Min Peng; Junfeng Wang; Qian Wu; Chao Yan; Qingli Bo; Jie Wang; Chenlin Shen; Panzhu Qin (Analytica Chimica Acta, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Mineral residue accelerant-enhanced anaerobic digestion of cow manure: An evaluation system of comprehensive performance - Sining Yun; Tian Xing; Yi Wang; Rong Chen; Feng Han; Chen Zhang; Ming Zou (Science of The Total Environment, 2023)

Landscapes drive the dispersal of Monochamus alternatus, vector of the pinewood nematode, revealed by whole-genome resequencing - Xiaohong Han; Yechen Li; Wanlong Huang; Rong Wang; Xia Hu; Guanghong Liang; Shiguo Huang; Chunlan Lian; Feiping Zhang; Songqing Wu (Forest Ecology and Management, 2023)

Molecular mechanisms of interrod spacing-mediated osseointegration via modulating inflammatory response and osteogenic differentiation - Meng Yu; Hongwei Yang; Bo Li; Rong Wang; Yong Han (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Progress in the preparation, application, and recycling of black phosphorus - Ying Han; Xiaolong Rong; Mingxin Wang Yingang Xue; Hao Dai; Yuxuan Liu (Chemosphere, 2023)

Effects of synthetic astaxanthin and Haematococcus pluvialis on growth, antioxidant capacity, immune response, and hepato-morphology of Oncorhynchus mykiss under cage culture with flowing freshwater - Wei Zhao; Han-Lin Wei; Meng-Die Chen; Rong Yao; Zi-Qiao Wang; Jin Niu (Aquaculture, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Associations of essential element serum concentrations with autism spectrum disorder - Jing Wu; Dongfang Wang; Lailai Yan; Meixiang Jia; Jishui Zhang; Songping Han; Jisheng Han; Jingyu Wang; Xi Chen; Rong Zhang (Environmental Science and Pollution Research, 2022)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Metabacillus rhizolycopersici sp. nov., Isolated from the Rhizosphere Soil of Tomato Plants - Rong Ma; Shan-Wen He; Xing Wang; Kyu Kyu Thin; Ji-Gang Han; Xiao-Xia Zhang (Current Microbiology, 2022)

Simulating the canopy photosynthesis of Qinghai spruce (Picea crassifolia Kom.) in the Qilian Mountains, Northwestern China - Junjie Liu; Juan Wang; Yanan Han; Shunjie Yuan; Yunfei Gao; Zhanlei Rong; Chuanyan Zhao (New Forests, 2022)

Impacts of Human Activities and Climate Change on Water Storage Changes in Shandong Province, China - Longyun Deng; Zhen Han; Weixing Pu; Rong Bao; Zheye Wang; Quanyuan Wu; Jianmin Qiao (Environmental Science and Pollution Research, 2022)

Novel blood-based hypomethylation of SH3BP5 is associated with very early-stage lung adenocarcinoma - Rong Qiao; Runbo Zhong; Chunlan Liu; Feifei Di; Zheng Zhang; Ling Wang; Tian Xu; Yue Wang; Liping Dai; Wanjian Gu; Baohui Han; Rongxi Yang (Genes & Genomics, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Association Between Essential Metal Elements and the Risk of Autism in Chinese Han Population - Jiahui Ma; Jing Wu; Haibin Li; Jingyu Wang; Jisheng Han; Rong Zhang (Biological Trace Element Research, 2022)

Activation of autophagy reverses gemcitabine-induced immune inhibition of RAW264.7 macrophages by promoting TNF-α, IL-6 and MHC-II expression - Shanshan Jiang; Rong Wang; Lu Han; Kudelaidi Kuerban; Li Ye; Shu Pan; Shengnan Li; Yongfang Yuan (Immunologic Research, 2021)
This research aims to investigate the effect of gemcitabine (GEM) on various activities and functions of macrophages. Phagocytosis, cell autophagy and reactive oxygen species (ROS) were analysed by laser scanning confocal microscope. The cell cycle status and major histocompatibility complex II (MHC-II) expression were examined by flow cytometry. Inflammatory cytokine secretion such as tumour necrosis factor α (TNF-α) and interleukin 6 (IL-6) was detected by Elisa assay. The expression of proteins was analysed by western blot method. The results revealed that GEM-induced immune inhibition of M1-type RAW264.7 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS). We also found that GEM inhibited autophagy, as evidenced by the reduced formation of autophagosome-like vacuoles and autophagosomes. Further study showed that incubation of activated macrophages with the autophagy inhibitor 3-MA induced immune suppression. In contrast, treatment with the autophagy inducer trehalose (Tre) restored phagocytosis, TNF-α and IL-6 secretion, and MHC-II expression in GEM-induced immune-inhibited macrophages. GEM reduced immune effect of M1-type RAW264.7 macrophages via inhibiting TNF-α, IL-6 and MHC-II expression. Furthermore, activation of autophagy by Tre reversed GEM-induced immune inhibition of RAW264.7 macrophages.

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Rhizobium rhizolycopersici sp. nov., Isolated from the Rhizosphere Soil of Tomato Plants in China - Kyu Kyu Thin; Shan-Wen He; Xing Wang; Yao Wang; Ma Rong; Ji-Gang Han; Xiaoxia Zhang (Current Microbiology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Bacterial and Archaeal Communities within an Ultraoligotrophic, High-altitude Lake in the Pre-Himalayas of the Qinghai-Tibet Plateau - Rong Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Derui Zhu (Indian Journal of Microbiology, 2020)

Climate-related risks in the construction of Xiongan New Area, China - Yujie Wang; Lianchun Song; Zhenyu Han; Yaoming Liao; Hongmei Xu; Jianqing Zhai; Rong Zhu (Theoretical and Applied Climatology, 2020)
In the paper, we analyze the climate-related risks of rainstorm floods, droughts and water shortages, high temperatures, and heavy hazes in the Xiongan New Area. A warming and drying trend was seen in Xiongan New Area during 1961–2018, as evidenced by the increase in the number of high-temperature days and the maximum rainfall intensity per hour, a decrease in surface water resources and groundwater levels, a reduction in wind speeds, and weakening of the self-purification capacity of the atmosphere. It is estimated that the areas at high risk of floods and heats will increase by 15.7 and 15.6% in around 2035 relative to 1986–2005, respectively. Although the runoff in the Daqing River Basin will increase, the construction of Xiongan New Area means that the imbalance between the supply and demand of water resources will remain. Climate change adaptation measures should therefore be improved in the planning and construction of Xiongan New Area. Finally, we discuss the approaches to address climate-related risks in this new area.

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Decrypting the crosstalk of noncoding RNAs in the progression of IPF - Yujuan Wang; Han Xiao; Fenglian Zhao; Han Li; Rong Gao; Bingdi Yan; Jin Ren; Junling Yang (Molecular Biology Reports, 2020)
Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibrosis; however, the mechanisms underlying their roles are largely unknown. In this review, we systematically summarized the recent advances regarding the crucial roles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) and crosstalk among them in the development of IPF. The perspective for related genes was well highlighted. In summary, ncRNA and their interactions play a key regulatory part in the progression of IPF and are bound to provide us with new diagnostic and therapeutic targets.

Effect of different seasons (spring vs summer) on the microbiota diversity in the feces of dairy cows - Han Li; Rong Li; Huijun Chen; Jing Gao; Yu Wang; Yifeng Zhang; Zhili Qi (International Journal of Biometeorology, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Zizania aquatica–duck ecosystem with recycled biogas slurry maintained crop yield - Guiliang Wang; Jianghong Zhang; Xiangming Kou; Shouhong Wang; Jianfeng Liu; Rong Xu; Guangming Han; Leiming Wu; Lingyu Zhu (Nutrient Cycling in Agroecosystems, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

HL2 on chromosome 7D of wheat (Triticum aestivum L.) regulates both head length and spikelet number - Hongni Yao; Quan Xie; Shulin Xue; Jing Luo; Jikang Lu; Zhongxin Kong; Yongpan Wang; Wenling Zhai; Nan Lu; Rong Wei; Yang Yang; Yuzhou Han; et al. (Theoretical and Applied Genetics, 2019)

Extracellular ATP released by copper stress could act as diffusible signal in alleviating the copper stress-induced cell death - Ling-Yun Jia; Jing-Yue Bai; Kun Sun; Rong-fang Wang; Han-Qing Feng (Protoplasma, 2019)

Chloroplast proteomic analysis of Triticum aestivum L. seedlings responses to low levels of UV-B stress reveals novel molecular mechanism associated with UV-B tolerance - Limei Gao; Xiaofei Wang; Yongfeng Li; Rong Han (Environmental Science and Pollution Research, 2019)

Efficiency of maternal-fetal transfer of perfluoroalkyl and polyfluoroalkyl substances - Yiwen Wang; Wenchao Han; Caifeng Wang; Yijun Zhou; Rong Shi; Eva Cecilie Bonefeld-Jørgensen; Qian Yao; Tao Yuan; Yu Gao; Jun Zhang; Ying Tian (Environmental Science and Pollution Research, 2019)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Changes by cadmium stress in lipid peroxidation and activities of lipoxygenase and antioxidant enzymes in Arabidopsis are associated with extracellular ATP - Qin-zheng Hou; Guang-ji Ye; Rong-fang Wang; Ling-yun Jia; Jun-yu Liang; Han-qing Feng; Jing Wen; Dai-long Shi; Qing-wen Wang (Biologia, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Microglia activation contributes to quinolinic acid-induced neuronal excitotoxicity through TNF-α - Wei Feng; Yan Wang; Zi-Qi Liu; Xuan Zhang; Rong Han; You-Zhu Miao; Zheng-Hong Qin (Apoptosis, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Syndecan-4 regulates the bFGF-induced chemotactic migration of endothelial cells - Ran Li; Han Wu; Jun Xie; Guannan Li; Rong Gu; Lina Kang; Lian Wang; Biao Xu (Journal of Molecular Histology, 2016)

Molecular cloning and functional analysis of two phosphate transporter genes from Rhizopogon luteolus and Leucocortinarius bulbiger, two ectomycorrhizal fungi of Pinus tabulaeformis - Rong Zheng; Jugang Wang; Min Liu; Guozhen Duan; Xiaomin Gao; Shulan Bai; Yachao Han (Mycorrhiza, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Tetrodotoxin detection and species identification of pufferfish in retail roasted fish fillet by DNA barcoding in China - Nan Li; Qing Shen; Jiahui Wang; Chunhui Han; Rong Ji; Fengqin Li; Tao Jiang (Food Additives & Contaminants: Part A, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Relationships between heavy metal concentrations in soils and reclamation history in the reclaimed coastal area of Chongming Dongtan of the Yangtze River Estuary, China - Chao Ma; Rong Zheng; Jiale Zhao; Xiumei Han; Li Wang; Xiaojiang Gao; Chaosheng Zhang (Journal of Soils and Sediments, 2015)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Applying support vector regression analysis on grip force level-related corticomuscular coherence - Yao Rong; Xixuan Han; Dongmei Hao; Liu Cao; Qing Wang; Mingai Li; Lijuan Duan; Yanjun Zeng (Journal of Computational Neuroscience, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Establishment of a Spinal Cord Injury Model in Adult Rats by an Electrocircuit-Controlled Impacting Device and its Pathological Observations - Yun Wang; Chun-feng Liu; Qi-ping Wang; Heng Gao; Han-rong Na; Ru-tong Yu (Cell Biochemistry and Biophysics, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Identification and characterization of Pestalotiopsis spp. causing twig blight disease of bayberry (Myrica rubra Sieb. & Zucc) in China - Hai-Ying Ren; Gang Li; Xing-Jiang Qi; Li Fang; Han-Rong Wang; Ji-Guang Wei; Shaobin Zhong (European Journal of Plant Pathology, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Survey of aflatoxin M1 in raw milk in the five provinces of China - Nan Zheng; Jia-Qi Wang; Rong-Wei Han; Yun-Peng Zhen; Xiao-Min Xu; Peng Sun (Food Additives & Contaminants Part B-Surveillance, 2013)

Polymorphisms of UGT1A9 and UGT2B7 influence the pharmacokinetics of mycophenolic acid after a single oral dose in healthy Chinese volunteers - Dong Guo; Liang-Fang Pang; Yang Han; Hong Yang; Guo Wang; Zhi-rong Tan; Wei Zhang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Establishment of reference mandibular plane for anterior alveolar morphology evaluation using cone beam computed tomography - Rong-yang Wang; Min Han; Hong Liu; Chun-ling Wang; Hong-hong Xian; Lei Zhang; Shi-jie Zhang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

A mini review of MAR-binding proteins - Tian-Yun Wang; Zhong-Min Han; Yu-Rong Chai; Jun-He Zhang (Molecular Biology Reports, 2010)

Role of secretory protease inhibitor SPINK3 in mouse uterus during early pregnancy - Wen Chen; Bing-Chen Han; Rong-Chun Wang; Gao-Feng Xiong; Jing-Pian Peng (Cell and Tissue Research, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Karyotypic, palynological, and RAPD study on 12 taxa from two subsections of section Idaeobatus in Rubus L. and taxonomic treatment of R. ellipticus, R. pinfaensis, and R. ellipticus var. obcordatus - Xiao-Rong Wang; Hao-Ru Tang; Han-Wu Zhang; Bi-Feng Zhong; Wu-Feng Xia; Yuan Liu (Plant Systematics and Evolution, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Changes of Porcine Growth Hormone and Pituitary Nitrogen Monoxide Production as a Response to Cadmium Toxicity - Xin-Yan Han; Qi-Chun Huang; Bo-Jing Liu; Zi-Rong Xu; Yi-Zhen Wang (Biological Trace Element Research, 2007)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Identification of differentially expressed genes in seeds of two near-isogenic Brassica napus lines with different oil content - Rong-Jun Li; Han-Zhong Wang; Han Mao; Ying-Tang Lu; Wei Hua (Planta, 2006)

Potentiating effect of tramadol on methamphetamine-induced behavioral sensitization in mice - Jian-Hui Liang; Keng Wang; Hong-Lei Sun; Rong Han (Psychopharmacology, 2006)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)

Ribozyme-mediated resistance to rice dwarf virus and the transgene silencing in the progeny of transgenic rice plants - Shengcheng Han; Zujian Wu; Huaiyi Yang; Rong Wang; Yin Yie; Lianhui Xie; Po Tien (Transgenic Research, 2000)